Toward Development of A.D.A. – Advanced Distributed Assistant - Freire, Fernando; Rosa, Thatiane; Feulo, Guilherme; Elmadjian, Carlos; Cordeiro, Renato; Moura, Shayenne; Andrade, Acácio; de Omena, Lucy Anne; Vicente, Augusto; Marques, Felipe; Sheffer, Aléxia; Hideki, Otávio; et al. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2020: Anais do XXI Simpósio em Sistemas Computacionais de Alto Desempenho, 2020)
The A.D.A. – Advanced Distributed Assistant – project aims to build a smart distributed personal assistant, that is, a virtual agent that can interact with the user through an ecosystem of devices, such as IoT (Internet of Things), by voice commands in Portuguese. The project is divided into six scientiﬁc initiation subprojects from different areas of computer science, where each one is co-advised by a graduate student. An open source proof of concept is being created in order to demonstrate the assistant capabilities and its applications in public and private domains.